MNGI-24. PREDICTORS OF VISUAL OUTCOMES IN SPHENO-ORBITAL MENINGIOMA SURGERY ENDORSE EARLY MAXIMUM SAFE SURGERY AND INTENSIVE FOLLOW-UP OF PATIENTS WITH MULTIPLE MENINGIOMA - Najafabadi, Amir Zamanipoor (Neuro Oncol, 2018)
OBJECTIVE: Most Spheno-Orbital Meningioma (SOM) series include patients over a period of multiple decades, while surgical techniques have improved over the years. In addition, predictors of visual outcomes and progression free survival (PFS) have not yet been systemically assessed. The aim of this study was to assess predictors of visual outcomes and PFS in a recent SOM cohort. METHODS: Consecutive patients operated by a team of a neurosurgeon and orbital surgeon in the Leiden University Medical Center between June 2015-December 2017 were included. Pre- and postoperative visual acuity (Snellen chart), visual field deficit (Humphrey field analyser, in decibel [dB]), and relative proptosis (exophthalmometry) were compared with the Wilcoxon signed-rank test. Predictors of visual outcomes were assessed with linear regression analysis. Predictors of PFS (definition: need for reintervention) with the log-rank test. RESULTS: Eight patients presented with impaired visual acuity, which improved in 88% (preoperative: 0.8, postoperative: 1.1, p=0.012). All 16 patients presented with visual field deficits, which improved in 86% (preoperative: -8.4dB, postoperative: -3.8dB, p=0.008). Also all patients presented with proptosis, which improved in 86% (preoperative: 4.5mm, postoperative: 2.9mm, p=0.013) Strongest predictors for postoperative visual acuity, visual field deficits and persistent proptosis were preoperative visual acuity (p=0.001), visual field (p<0.001) and proptosis (p=0.017), respectively. Predictors for PFS were Simpson grade (p=0.048) and number of meningioma tumours (p=0.017). CONCLUSION: In our cohort, all visual outcomes and proptosis improved significantly after surgery. We recommend early surgery after diagnosis, as patients who present with greatly impaired or deteriorated visual function are less likely to have normal postoperative visual outcomes. In addition, we recommend more frequent and tailored follow-up for patients after a Simpson grade II-V resection of the SOM or with multiple meningioma.